Pengaruh Flash Sale Dan Hedonic Shopping Motivation Terhadap Impulse Buying Melalui Positive Emotion (Studi Pada Pengguna E-Commerce Shopee - Rizal, Naufa Arizka; Suyono, Suyono (Universitas Trunojoyo Madura, 2025)
The purpose of this study was to measure and determine the effect of Flash Sale and Hedonic Shopping Motivation on Impulse Buying through Positive Emotion with Shopee E-Commerce Users. This type of research is quantitative, the data collection method used is purposive sampling (non-probability). The population in this study were people from Bangkalan Regency who shopped online at Shopee e-commerce in the last six months, from October 2024 to April 2025. The sample used was 97 respondents with primary data sources from distributing questionnaires. The data analysis technique used is Structural Equation Modeling (SEM) SmartPLS 4.0.The results of the research analysis conducted, it shows that the Flash Sale variable mediated by Positive Emotion on Impulse Buying obtained a t-statistic value of 1.657 t-table of 0.1698, which means H0 is rejected and H1 is accepted. Meanwhile, the Hedonic Shopping Motivation variable mediated by Positive Emotion on Impulse Buying obtained a t-statistic value of 1.778 t-table of 0.1698, which means H0 is rejected and H1 is accepted. Thus it can be concluded that Flash Sale (X1), and Hedonic Shopping Motivation (X2) have a positive effect on Impulse Buying (Y) through Positive Emotion (Z) on E-commerce Shoppe.